Financial Ratio Analysis To Measure Company Financial Performance At Pt. Indofood Sukses Makmur 2020-2024 Period - Delvini Andari Gea; Heriyati Chrisna; Fitri Yani Panggabean (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the financial performance of PT. Indofood Sukses Makmur Tbk during the 2020–2024 period using financial ratio analysis, including liquidity, solvency, activity, profitability, and market value ratios. The study employed a quantitative descriptive approach with secondary data in the form of annual financial reports obtained from the company's official website and the Indonesia Stock Exchange. The analysis was conducted by comparing the company's financial ratios to industry standards and analyzing year-over-year trends. The results show that the company's liquidity and solvency performance have improved, reflecting its ability to meet short-term obligations and an increasingly stable capital structure. However, activity ratios indicate a decline in asset utilization efficiency after 2022. Furthermore, the profitability ratio, measured by Return on Equity (ROE), tends to decline, while Earnings Per Share (EPS) fluctuates. Overall, the company needs to improve operational efficiency and asset optimization to drive increased profitability and company value.